Temporal trends and sex differences in sudden cardiac death in the Copenhagen City Heart Study. Issue 16 (21st May 2021) - Ågesen, Frederik Nybye; Lynge, Thomas Hadberg; Blanche, Paul; Banner, Jytte; Prescott, Eva; Jabbari, Reza; Tfelt-Hansen, Jacob
Abstract : Objective: More knowledge about the development of sudden cardiac death (SCD) in the general population is needed to develop meaningful predictors of SCD. Our aim with this study was to estimate the incidence of SCD in the general population and examine the temporal changes, demographics and clinical characteristics. Methods: All participants in the Copenhagen City Heart Study were followed from 1993 to 2016. All death certificates, autopsy reports and national registry data were used to identify all cases of SCD. Results: A total of 14 562 subjects were included in this study. There were 8394 deaths with all information available, whereof 1335 were categorised as SCD. The incidence of SCD decreased during the study period by 41% for persons aged 40–90 years, and the standardised incidence rates decreased from 504 per 100 000 person-years (95% CI 447 to 569) to 237 per 100 000 person-years (95% CI 195 to 289). The incidence rate ratio of SCD between men and women ≤75 years was 1.99 (95% CI 1.62 to 2.46). The proportion of SCD of all cardiac deaths decreased during the observation period and decreased with increasing age. Men had more cardiovascular comorbidities (OR 1.34, 95% CI 1.07 to 1.68, p<0. 01), and SCD was the first registered manifestation of cardiac disease in 50% of all cases. Conclusion: The incidence of SCD in the general population has declined significantly during the study period but should be further investigated for more recent variations as well as novel risk predictors for persons with low to medium risk of SCD.